Design and development of inikasir application as an android-based payment transaction media at sederhana restaurant - Gustina, Revani (Ebiz Prima Nusa, 2024)
Payment transactions at sederhana restaurant are still done manually so they are less effective and efficient. Using this manual method is prone to errors in calculating the amount of payment, it takes some time to write proof of payment transactions using notes, it is difficult to control food stocks and sales reports that still use books. Android is one of today's advanced technologies that has many functions. The Inikasir application is a system created to make it easier for companies to make payment transactions. The purpose of this research is to design the Inikasir application as an Android-based payment transaction medium that has a function to make it easier for users to calculate transactions automatically, store sales report data and generate payment receipts. more quickly and efficiently. This application is made using flutter framework and Android Studio. System testing uses black box testing which aims to find out if an application can run properly according to the functions expected before. In addition, testing was carried out on cashier employees and rice shop owners to find out the state of sales transactions before and after the application. The results of this test state that using the Inikasir application as an Android-based payment transaction medium makes payment transactions and viewing sales reports faster. Keywords: Application, transaction, android